2015
DOI: 10.1557/jmr.2015.329
|View full text |Cite
|
Sign up to set email alerts
|

Ion size effects on thermoluminescence of terbium and europium doped magnesium orthosilicate

Abstract: Thermoluminescence (TL) and radioluminescence (RL) are reported over the temperature range 25-673 K from MgSiO 4 :Tb and MgSiO 4 :Eu. The dominant signals arise from the transitions within the Rare Earth (RE) dopants, with limited intensity from intrinsic or host defect sites. The Tb and Eu ions distort the lattice and alter the stability of the TL sites and the peak TL temperature scales with the Tb and Eu ion size. The larger Eu ions stabilize the trapped charges more than for the Tb, and so the Eu TL peak t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…However, in closely linked sites electron tunneling would initially favour the lower level transitions, as seen in this Er data. The same possibility has recently been reported for Tb and Eu doped magnesium orthosilicate dosimeters [34,35] and a more general review includes examples from crystalline material [36]. The possibility of such tunneling has frequently been discussed but these RE emission spectra produce TL that offers direct evidence.…”
Section: Effects Of Thermal Treatmentsmentioning
confidence: 73%
“…However, in closely linked sites electron tunneling would initially favour the lower level transitions, as seen in this Er data. The same possibility has recently been reported for Tb and Eu doped magnesium orthosilicate dosimeters [34,35] and a more general review includes examples from crystalline material [36]. The possibility of such tunneling has frequently been discussed but these RE emission spectra produce TL that offers direct evidence.…”
Section: Effects Of Thermal Treatmentsmentioning
confidence: 73%
“…This clarity of separation of peak temperature with increasingly higher starting levels of the Er occurs because all the transitions are from higher levels down to a single ground state (i.e. in contrast with say the Tb and Eu data discussed earlier) [15]. From the modelling of Fig.…”
Section: Examples Of Wavelength Tl Differences From Single Crystal Samentioning
confidence: 73%
“…The changes are not random but, as shown below, are linked to the higher-energy states of the ions that define the emission wavelength. Two clear examples of this effect are apparent in the spectra of TL from terbium or europium doped magnesium orthosilicate dosimetry powder [15]. Conceptually, these are not ideal examples as the dosimetry powders are sensitive to dopant concentration and their thermal processing.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…3(b). Visual inspection of the collected data in terms of wave length (k) offers I(k)dk versus k. This is not ideal as the science requires an energy view of I(E)dE versus E. 17 Invariably the wave length presentation is distorted and broadened at longer wavelengths. In the energy domain plot, the true band is symmetric, as shown by the transformation to the energy plot of Fig.…”
Section: A High Temperature Tl Datamentioning
confidence: 99%
“…Previous studies have indicated that collecting the TL spectra at low temperature adds considerably by both monitoring the intrinsic defects [16][17][18][19] and revealing the presence of inclusions. Similarly, radioluminescence (RL), obtained during heating whilst exciting the materials with x-rays, discloses a range of imperfections that may not be evident in the more limited TL data.…”
Section: Introductionmentioning
confidence: 99%